PROYEK PEMBELAJARAN AKUNTANSI UNTUK SDG BIDANG PENDIDIKAN - Imelda, Elsa; Imelda Rani; Simina, Juni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The Sustainable Development Goals proclaimed by the UN are also implemented in Indonesia as a member of the UN. Of the 17 development areas, one of them is the education sector. Education that leads to skills is one of the goals of the SDGs in the field of education. Students are expected to become independent quickly if they have special skills. One of the skills that can be mastered quickly by high school students is accounting skills. Even though accounting is often difficult to understand, the PKM team from Untar will use project-based learning techniques from for Tarsisius 1 High School students. The results of the activity were really felt by the students and the students were able to understand accounting journaling more easily.